Kobiety na tropie. Kategoria ?kobiecości? w kryminałach współczesnych polskich pisarek = Women on the track. The category of "femininity" in crime novels by contemporary polish writers - Poświatowska, Julia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The publication concerns the crime novels by contemporary Polish writers, analysed in terms ofthe models of women?s identity and subjectivity. The author takes a closer look at literary patternsadopted by the aforementioned writers and attempts to decide whether they portray characters intheir books through borrowing a stereotypical character of a male detective (from a classic crimenovel), or whether they create entirely new and original female characters.
Keywords: literatura polska - 21 w. - tematyka; literatura kobieca; powieść kryminalna